Stepping Out of The Cultural Identity: A Critical Analysis of Cathy Songâ€™s Memory Poetry - Setia Sari, Winda (Talenta Publisher, 2019)
Cathy Song, a Chinese-Korean ancestry woman poet, grew up in Hawaii, America. In â€œWhat Belongs to Youâ€, a poem taken from her second poetry publication, she chronicles the memory of a child who is trapped between her dream and devotion. The theme of the poem is portrayed in a strong poetic devices. The poems lean in vivid visual imageries to evoke to the poetâ€™s life memory. The speaker of What Belongs to You dreams of having the freedom and attempts to escape from her parental tie. Ironically, she finds herself devote to her family and tradition. The poems use past materials ranging from domestic domain and landscape which define the speakerâ€™s personal memory. Comparing than Cathyâ€™s Song first poetry publication, arguably, the cultural materials in the poem cannot be traced through Songâ€™s poetic devices as an ethnic woman poet. In fact, song locates the dream and devotion in visual imageries and nostalgic tones in a general way. This is true; Song has denied herself as a cultural visionary. Song merely mines the memory from the point of view and identity of a woman, leaving her cultural traits behind.